2012
DOI: 10.1016/j.cub.2012.09.044
|View full text |Cite
|
Sign up to set email alerts
|

A GRAS-Type Transcription Factor with a Specific Function in Mycorrhizal Signaling

Abstract: Legumes establish mutualistic associations with mycorrhizal fungi and with nitrogen-fixing rhizobial bacteria. These interactions occur following plant recognition of Nod factor from rhizobial bacteria and Myc factor from mycorrhizal fungi. A common symbiosis signaling pathway is involved in the recognition of both Nod factor and Myc factor and is required for the establishment of these two symbioses. The outcomes of these associations differ, and therefore, despite the commonality in signaling, there must be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
269
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(284 citation statements)
references
References 18 publications
10
269
1
4
Order By: Relevance
“…GRAS-domain proteins have already been shown to function during AM associations, with RAM1 playing a major role [6], and NSP1/NSP2 playing minor roles [7][8]. We found that OsRAM1 can complement Medicago ram1, indicating that OsRAM1 served the same function as MtRAM1 during mycorrhizal colonization (Supplementary information, Figure S7).…”
Section: Dear Editormentioning
confidence: 54%
See 1 more Smart Citation
“…GRAS-domain proteins have already been shown to function during AM associations, with RAM1 playing a major role [6], and NSP1/NSP2 playing minor roles [7][8]. We found that OsRAM1 can complement Medicago ram1, indicating that OsRAM1 served the same function as MtRAM1 during mycorrhizal colonization (Supplementary information, Figure S7).…”
Section: Dear Editormentioning
confidence: 54%
“…Taken together, our results imply that a large complex of GRAS-domain proteins functions in the AM symbiosis with at least SLR1, DIP1 and RAM1 interacting together. As MtRAM1 has been shown to bind to the promoter of an AM-induced gene [6,9], we propose that npg this GRAS-domain protein complex is directly associated with mycorrhizal gene expression. The mycorrhizal symbiosis is extremely ancient and was found in the earliest land plants, suggesting that the role of DELLAs in the AM symbiosis is probably very ancient.…”
Section: Dear Editormentioning
confidence: 99%
“…Moreover, GRAS proteins have been reported to form homodimers and heterodimers with other GRAS family members and this is likely important for their transcriptional regulation function (Itoh et al, 2002;Cui et al, 2007;Heo et al, 2011;Zhang et al, 2011;Gobbato et al, 2012;Murakami et al, 2013;Xue et al, 2015). Here, our structure of Os-SCL7 was determined in a dimer with helices A12, A79, and A69 at the dimer interface.…”
Section: Discussionmentioning
confidence: 99%
“…In rhizobium legume symbiosis (RLS), signaling through the SSP ultimately activates transcription factors that control infection and nodule development (23). A similar model is proposed for AM symbiosis, and GRAS factors that regulate hyphopodia development (24) and cortical colonization levels have been identified (25), but regulators specific for arbuscule formation are unknown. Transcript profiling and promoter-reporter gene analyses indicate complex changes in plant gene expression in the root cortex during arbuscule development, suggesting that multiple signaling pathways may be involved in arbuscule formation (14,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%